Komponen Kimia dan Sifat Antioksidan Kopal (Chemical Components and Anti-oxidative Properties of Copal) - Ganis Lukmandaru (Jurnal Ilmu dan Teknologi Kayu Tropis, 2017)
Analysis of the chemical components and anti-oxidative properties of  copals were conducted. Copal samples were procured from 6 trees of Agathis borneensis stand established in Banyumas Timur Forest Management Unit. SNI 7634:2011 was referred in chemical analysis of the samples. The copals were dissolved in toluene and ethanol, consecutively. Neutral and acidic fractions were obtained by fractionation of toluene soluble extracts. Total phenolic content of ethanol soluble extracts were determined by Folin-Ciolcateu method. Copal components were detected by GC-MS analysis and anti-oxidative properties were examined by 1,1-diphenyl-2-picryl-hydrazyl (DPPH) test. Dirt content, ash content, and acid number were found in the range of 6.25-22.63%, 0.05-0.16%, and 190-378, respectively. Solubility in toluene was of 19-46% and solubility in ethanol was of 53-81% based on extract weights. Neutral and acidic fractions based on toluene extract were in the range of 20-44% and 56-80%, respectively. The components of copal were assigned as resin acid (agatholic acid), neutral diterpene derivates (agathadiol, labdanenone, labdadienedioat), and alcohol monoterpene. Total phenolic content was in the range of 12-22 mg g-1 extract equivalent to gallic acid . Anti-oxidative values of the presently investigated copal were comparatively low, regardless of the copals were indicated to contain phenolic compoundsKeywords: Agathis borneensis, antioxidative properties, copals, extractives,  resin